THE APPLICATION OF THE DICTOGLOSS TECHNIQUE TO IMPROVE STUDENTS' ACHIEVEMENT IN LISTENING COMPREHENSION - Khairun Niswa; Muhammad Hasyimsyah Batubara; Nasyupit Nasyupit (Jurnal As-Salam, 2022)
Listening comprehension plays the most crucial role in building communication skills. However, students always think it is challenging to listening lessons. And the reason is that sometimes they are bored and not interested in the material. In addition, inappropriate methods and techniques may cause students to lack interest and motivation to learn. The author is interested in conducting research with the dictogloss technique to overcome the difficulties faced by students in learning activities. The purpose of this study was to determine the learning process of listening comprehension and to find out the advantages of the dictogloss technique in class X IPA 1 at MAN Pegasing. This study uses classroom action research, data collection techniques using pre-test and post-test, and questionnaires to determine the advantages of the dictogloss technique. The results of this study indicate that the dictogloss technique effectively improves student achievement in listening comprehension at MAN Pegasasing. Furthermore, the students agreed that the dictogloss technique is one of the exciting techniques and can improve student achievement in listening.